Kajian Amalan Keselamatan dan Kesihatan Pekerjaan Berkesan (KKP) untuk Pengurusan Pekerja di Industri Pembinaan - Noor Hazuan, Nurul Nazurah; Kasim, Narimah; Mohd Noh, Hamidun; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2022)
The construction industry in Malaysia often faces several challenges in Occupational Safety and Health (OSH). There are several challenges identified such as lack of knowledge and expertise in managing OSH, financial constraints, increased operating costs as well as the provision of a more comfortable and conducive workplace. Therefore, the focus of this study is to examine the effective OSH in the management of workers in the construction industry. The objective of this study is to identify current practices, challenges and propose new approaches to ineffective OSH for employee management in the construction industry. This study uses a quantitative method by using a questionnaire as an instrument and distributing it to respondents. The respondents of this study are G7 grade contractors consisting of project managers, site managers, site engineers, architects, safety and health officers, and materials surveyors involved in activities at construction sites in the state of Johor. The data collected in this study were analyzed using descriptive methods to obtain information from the questionnaire using Statistical Package for the Social Science (SPSS) software to achieve the objectives of the study. The results of the study found that significant current practices ineffective practice are safety training programs given before starting a project, knowledge challenges of the Occupational Safety and Health Act 1994 (OSHA 1994), and creating effective OSH programs in cultivating OSH. In conclusion, this study can provide information with respect to effective occupational safety and health practices in the management of construction workers involved in construction projects.